EVALUASI PROGRAM PENDIDIKAN DAN PELATIHAN KEPEMIMPINAN TINGKAT IV DALAM KEBIJAKAN PENGEMBANGAN KOMPETENSI ASN DI PEMERINTAH KABUPATEN LAHAT - Dian Novita Fajar Sari (Jurnal Caraka Prabu, 2021)
This study aims to evaluate the Level IV Leadership Education and Training Program (Diklatpim) using the COPP evaluation model developed by Stufflebeam. The CIPP evaluation model is expected to produce a complex evaluation of the 2016 Level IV Diklatpim program in the Lahat District Government. Based on the use of the evaluation model, the qualitative research method with a case study approach was chosen by the researcher. Data collection was carried out by interviewing and studying documentation related to the implementation of Level IV Diklatpim in 2016. The informants in this study amounted to 15 people who came from the Agency for Personnel and Human Resources Development (BKPSDM) Lahat Regency, South Sumatra Province, Regional Human Resources Development Center. (BPSDMD) South Sumatra Province and participants of Level IV Training and Education in 2016 in the Lahat Regency government. When viewed from the aspects of the process and product implemented, the results of the study show that the 2016 Level IV Education and Training program in Lahat Regency has been in accordance with applicable regulations and is considered successful. However, based on the context and input aspects, there are several things that are not in accordance with the aims and objectives of the Level IV Diklatpim program in the Lahat Regency government.